The language factor – what exactly is it? Bilingual speakers of Russian and Finnish solving mathematical tasks - Ahlholm, Maria; Portaankorva-Koivisto, Päivi (NOMAD Nordic Studies in Mathematics Education, 2018)
A lack of knowledge of the language of instruction is often believed to be the main reason for low achievement among students with an immigrant background. We regard language as a tripartite unit comprising aspects of concept formation, pragmatic language usage and the linguistic form. In this theoretical framework, we report two case studies of bilingual, Russian and Finnish speaking students’ explanations of their procedures while solving mathematical tasks. The students’ linguistic processing varied in terms of conceptualization, pragmatic meaning-making and grammatical form. In a bilingual context, the labelling of concepts and meaning-making through argumentation are simultaneously processed in two languages.